2010
DOI: 10.1111/j.1750-3841.2010.01557.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Functional Properties and Antinutritional Factors of Extruded Hard‐to‐Cook Common Beans (Phaseolus vulgaris, L.)

Abstract: The biochemical and functional properties of 2 hard-to-cook common bean cultivars (Phaseolus vulgaris, L.) were investigated after the extrusion process. Beans of BRS pontal and BRS grafite cultivars were milled and extruded at 150 degrees C, with a compression ratio screw of 3 : 1, 5-mm die, and screw speed of 150 rpm. Extrudate flours were evaluated for water solubility (WS), water absorption index (WAI), oil absorption capacity (OAC), foaming capacity (FC), emulsifying activity (EA), antinutritional factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
73
1
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(86 citation statements)
references
References 36 publications
9
73
1
3
Order By: Relevance
“…Extrusion temperature of 85 C is sufficient for deactivating toxic lectins found in beans (Kelkar et al, 2012). The increased digestibility of starch and proteins and the reduction in lectin content due to extrusion processing increase the nutritional quality of the common bean flours (Batista et al, 2010).…”
Section: Water Absorption Index (Wai) and Water Solubility Index (Wsi)mentioning
confidence: 99%
See 2 more Smart Citations
“…Extrusion temperature of 85 C is sufficient for deactivating toxic lectins found in beans (Kelkar et al, 2012). The increased digestibility of starch and proteins and the reduction in lectin content due to extrusion processing increase the nutritional quality of the common bean flours (Batista et al, 2010).…”
Section: Water Absorption Index (Wai) and Water Solubility Index (Wsi)mentioning
confidence: 99%
“…EXT bean flours had significantly higher WSI than STC or raw bean flours (Table 1). Shear effect from extrusion may have degraded the starch producing more soluble molecules (Batista et al, 2010), thus increasing the solubility of EXT bean flour. Hernandez-Diaz, Quintero-Ramos, Barnard, and Balandran-Quintana (2007) observed that lower WSI correlates with lower degradation of starch.…”
Section: Water Absorption Index (Wai) and Water Solubility Index (Wsi)mentioning
confidence: 99%
See 1 more Smart Citation
“…The anti-nutritional factors limit the nutritional quality of beans because they reduce the activity of some enzymes, the biological action of certain chemical compounds, and the absorption of metabolites (RAMÍREZ-CÁRDENAS et al, 2008;BATISTA et al, 2010). Table 2 shows the anti-nutritional contents of the different bean cultivars.…”
Section: Anti-nutritional Factorsmentioning
confidence: 99%
“…In the case of beans, anti-nutritional factors such as phytates, protease and amylase inhibitors, lectins and polyphenols (tannins), reduce the activity of some enzymes and the absorption of metabolites (BATISTA et al, 2010).…”
Section: Introductionmentioning
confidence: 99%